2000
DOI: 10.1097/00003246-200001000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodilution versus inert gas rebreathing for estimation of effective pulmonary blood flow

Abstract: The RB method is a promising method for simultaneous noninvasive estimation of Qep and functional residual capacity in mechanically ventilated patients. However, further investigations are needed to evaluate potential problems of the method before it can be recommended for clinical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
2
30
0
3
Order By: Relevance
“…Recent studies have demonstrated that IGR measurements can be easily performed at rest and during exercise and therefore could add important information for optimizing the treatment of various cardiac disorders [17]. The previous results indicate good agreement of the IGR measurements with the clinically well-accepted thermodilution method as well as with Direct Fick calculations in smaller patient collectives [16,18,19,20,21]. However, thermodilution itself suffers from inaccuracies and is limited in clinical practice because of its invasiveness, cost and complexity [22, 23].…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies have demonstrated that IGR measurements can be easily performed at rest and during exercise and therefore could add important information for optimizing the treatment of various cardiac disorders [17]. The previous results indicate good agreement of the IGR measurements with the clinically well-accepted thermodilution method as well as with Direct Fick calculations in smaller patient collectives [16,18,19,20,21]. However, thermodilution itself suffers from inaccuracies and is limited in clinical practice because of its invasiveness, cost and complexity [22, 23].…”
Section: Introductionmentioning
confidence: 91%
“…Rückatmungsmethoden werden bereits seit langem zur nichtinvasiven Messung des Herzzeitvolumens sowohl bei spontan atmenden [26,29] als auch bei maschinell beatmeten Patienten benutzt [5,24].Ihre Verwendung in der klinischen Routine wurde jedoch bislang vor allem durch die Notwendigkeit einer akkuraten Gaskonzentrationsmessung erschwert.In der Vergangenheit wurde hierfür häufig die Massenspektrometrie herangezogen, die jedoch ein teures und zudem unhandliches Verfahren darstellt,das für den Routineeinsatz am Patientenbett wenig geeignet ist.…”
Section: Diskussionunclassified
“…Inhomogenitäten von Ventilation und Lungenperfusion sowie individuelle Unterschiede des Lungengewebsvolumens oder gar intraindividuelle Än-derungen des Lungengewebevolumens können jedoch zu methodischen Fehlern führen [13]. Von diesen Faktoren scheint insbesondere der Größe des Lungengewebevolumens eine entscheidende Bedeutung für die Messgenauigkeit von Rückatmungsverfahren zuzukommen [5], da das gut lösliche Lachgas nicht nur vom Kapillarblut, sondern auch vom Lungengewebe aufgenommen wird. Eine Über-schätzung des Lungengewebevolumens führt dabei zu einer Überschätzung der effektiven Lungendurchblutung durch die Rückatmungsmethode und umgekehrt.…”
Section: Limitierungen Der Studieunclassified
“…Short measurement cycles may lead to inaccuracies in beat-based methods such as CMR. IGR proved promising in previous investigations [4,5,6,7,8,9,10]. Measurement of CO over a range of consecutive heart beats may provide a realistic representation of the patient’s cardiac function in AF.…”
Section: Introductionmentioning
confidence: 93%
“…AF leads to a decrease in stroke volume and cardiac output (CO) according to Frank and Starling’s law of the heart [3]. The novel inert gas rebreathing (IGR) device (Innocor; Innovision, Odense, Denmark) based on the Fick principle obtained promising results when compared to other invasive [4,5,6,7,8] and non-invasive techniques [9,10,11]. The Fick principle is based on the observation that the total uptake of a substance by the peripheral tissues is equal to the product of blood flow to the peripheral tissues and the arterial-venous concentration difference in the substance.…”
Section: Introductionmentioning
confidence: 99%